“Un giogo salutare per l’intelligenza”: dogma religioso e libertà politica nella Democrazia in America di Tocqueville (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. In forma di premessa - 2. L’immensa maggioranza degli spiriti -  3. Una forma particolare della speranza: religione e libertà tra dispotismo e repubblica - 4. Dal dogma teologico al dogma della maggioranza -  5. Quale religione? - 6. Contro la patologia del dubbio - 7. Polvere intellettuale: il metodo filosofico tra America ed Europa - 8. Chiesa e Stato tra America e Francia - 9. Democrazia e Cattolicesimo americano - 10. Una democrazia cristiana: Stato e Chiesa nell’ ‘ultimo’ Tocqueville.“A salutary yoke on the intellect”: Religious Dogma and Political Freedom in Tocqueville’s Democracy in America.ABSTRACT: The essay examines the relationship between religion and politics in Tocqueville's thinking, with particular attention to the synergy between Christianity and the development of democratic institutions, studied by the author in the United States. In the two volumes of Democracy in America, he observes that the doctrine of Christianity, subject to a process of popularization characteristic of American social dynamism, constitutes an essential connective tissue, through which the principle of equality permeates custom, law and institutions. This stabilization function finds a fundamental premise in the separation between spiritual and temporal sphere, which allows the former not to be bent to the conveniences of the second and, above all, not to be subjected to attacks which, as in the French Revolution, have confused and condemned it with its institutional form under the ancien régime. Such a circumstance, according to Tocqueville, has deprived society of the fundamental ethical background that unites it, neglecting above all the powerful egalitarian message that he identifies as a general character of Christianity and in particular of Catholicism, which he thinks even more appropriate to the democracy as the Protestant faith and which, by acting on custom, would enable the establishment and development of an indigenous democratic model also in France.